Climate Policy, Stranded Assets, and Investors' Expectations - Suphi Sen; Marie-Theres von Schickfus (Center for Economic Studies and ifo Institute (CESifo), 2019)
Climate policies to keep global warming below 2℃ might render some of the world's fossil fuels and related infrastructure worthless prior to the end of their economic life time. Therefore, some energy-sector assets are at risk of becoming stranded. This paper investigates whether and how investors price in this risk of asset stranding. We exploit the gradual development of a German climate policy proposal aimed at reducing electricity production from coal and analyze its effect on the valuation of energy utilities. We find that investors take stranded asset risk into consideration, but that they also expect a financial compensation for their stranded assets.
Keywords: Q35; Q38; G14; 330; stranded assets; climate policy; expectations; utilities; event study